Long-Term Consequences Of Untreated Dental Trauma: A Comprehensive Analysis (Journal of Namibian Studies : History Politics Culture, 2022)
Untreated dental trauma can have significant long-term consequences, impacting oral health, function, aesthetics, and psychological well-being. This article provides a comprehensive analysis of the potential ramifications of neglected dental trauma. Key consequences include dental infections, tooth loss, periodontal complications, malocclusion, aesthetic concerns, and psychological distress. Additionally, untreated trauma can compromise overall oral health and necessitate more extensive and costly treatments in the future.